Altas concentrações de proteínas em dietas de matrizes de tilápia-do-Nilo e seus efeitos na atividade de enzimas digestivas durante o desenvolvimento inicial - Pereira, Mayara de Moura [UNESP] (2015)
The present study assessed the activity of gastric (pepsin), intestinal (aminopeptidase and alkaline phosphatase) and pancreatic (trypsin, amylase, lipase, protease) enzymes on the embryonic and larval development of Nile tilapia, Oreochromis niloticus, obtained from broodstock fed diets with four levels of crude protein. The experiment was carried out from January to June/2014, using 144 females and 48 males (3:1) distributed in 16 hapas (12 fish/hapa). Four treatments were used, composed of the following levels of crude protein (CP): 32, 38, 44 and 50 %, with four replications. The eggs were weighed (mg), quantified, kept in hatcheries (2.0 L), and separated according to treatment. Twenty-four (24) samples (300.0 mg) per treatment and four (4) samples per stage of embryonic and larval development [S0- cleavage, S1- blastula, S2- gastrula, S3- hatching, S4- 7 days posthatch and S5- 10 days posthatch] were collected, kept in cryogenic tubes and placed in liquid nitrogen (-196.0ºC) until the moment the digestive enzymes were analyzed. There were no differences between the values (P>0.05) of pepsin, aminopeptidase, trypsin, and amylase. However, different values were observed (P<0.05) for alkaline phosphatase (7 days posthatch), lipase (blastula), and protease (blastula and hatching) with regard to the four treatments. The results showed that diets with levels of crude protein offered to Nile tilapia broodstock influenced the activity of digestive enzymes during embryonic and larval periods, emphasizing that the nutrients ingested by the broodfish were transferred to the progeny. Thus, more studies on diets of broodstock should be conducted in order to provide additional information, not only with regard to levels of protein, but also energy, vitamins and minerals, as well as the interaction between them, and the use of physiological biomarkers for a successful fish farming